2021
DOI: 10.1016/j.ekir.2021.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Cyclical Cyclophosphamide and Steroids Versus Tacrolimus and Steroids in Primary Membranous Nephropathy

Abstract: Introduction Kidney Disease: Improving Global Outcomes (KDIGO) 2012 recommends cyclical cyclophosphamide plus glucocorticoids (GC) (modified Ponticelli regimen) or calcineurin inhibitors (CNIs) such as tacrolimus (TAC) or cyclosporine as the first-line agents for the management of primary membranous nephropathy (PMN) that is resistant to antiproteinuric therapy with renin-angiotensin system blockers. However, the long-term outcome of patients treated with CNIs is not known. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…At the end-point of six years after the beginning of treatment, 62% of participants in the cyclophosphamide/glucocorticoid group and 28% in the tacrolimus group maintained remission without relapse, and 88% of patients in the cyclophosphamide/glucocorticoid group vs 53% of patients in the tacrolimus group were in remission. This study confirmed the long-term superiority of six months of cyclophosphamide/glucocorticoid therapy vs one year of tacrolimus ( 62 ).…”
Section: Management Of Primary Membranous Nephropathysupporting
confidence: 80%
“…At the end-point of six years after the beginning of treatment, 62% of participants in the cyclophosphamide/glucocorticoid group and 28% in the tacrolimus group maintained remission without relapse, and 88% of patients in the cyclophosphamide/glucocorticoid group vs 53% of patients in the tacrolimus group were in remission. This study confirmed the long-term superiority of six months of cyclophosphamide/glucocorticoid therapy vs one year of tacrolimus ( 62 ).…”
Section: Management Of Primary Membranous Nephropathysupporting
confidence: 80%
“…However, neither cyclosporin A nor tacrolimus affects B cell differentiation [136,137]. Importantly, in studies of MN patients, both cyclophosphamide-and calcineurin inhibitor-based treatment regimens are clinically useful in MN, and can effectively reduce anti-PLA 2 R antibody titres in PLA 2 Rassociated MN, although greater, earlier and more sustained decreases were typically seen with cyclophosphamide-based regimens [138]. Patients on calcineurin inhibitors do not tend to go into durable remissions and have a high rate of immunological and clinical relapse after cessation of treatment.…”
Section: B Cells and The Treatment Of Membranous Nephropathymentioning
confidence: 99%
“…The efficacy of CNIs was also inferior in sustaining the remission in the long-term compared to the cyclic regimen with cyclophosphamide and steroids at 6 years post-treatment, 62% versus 28%, respectively. 85 Effective CNI regimens can include both tacrolimus 0.05–1 mg/kg/d aiming of 3–8 ng/mL, or cyclosporin 3.5 mg/kg/d with a goal of 125–225 ng/mL for 12 months. It is often used with low-dose prednisone (i.e., 10 mg/day).…”
Section: Cnismentioning
confidence: 99%